Hubungan Obesitas dengan Harga Diri (self-esteem)pada Remaja Putri SMA Negeri 13 Semarang - Wulandari, Priharyanti; Arifianto, Arifianto; Aini, Nurul (Jurusan Keperawatan FIKES UNSOED, 2016)
Obesity is a problem that is quite disturbing among young girls, because of the negative impact can lower self esteem. Based on RIKESDAS 2013, in Indonesia reached 32,9% and 29,05 in Central Java the purpose of this study was to analyze the relationship beetween obesity and self – esteem in young girl at SMA NEGERI 13 SEMARANG. This study uses correlation with cross sectional approach. The number of samples in this study were all young girls who are obese at SMA NEGERI 13 SEMARANG as many as 85 young girls, the way to take sampling using strantified random sampling. The instrument used was a questionare using spearman rank test. Result : The perccentage of 36 girls found obese overall I degree with positive self esteem 43 (79,6%). Obesity I grade with negative self esteem 11 girls (20,4%). Obesity II grade wih positive self esteem 5 girls (16,2%). Obesity II grade with negative self esteem 26 girls (83,9%). The statistical test result obtained using spearman rank test P value = 0.000≤0,05 (5%). The study prove the relationship beetween obesity with self esteem in young girl, the respondent expected to lose weight by improving diet and exercise as well as improving self esteem and have a positive view of what is owned